Intuitive parenting: understanding the neural mechanisms of parents’ adaptive responses to infants - Parsons, C; Young, K; Stein, A; Kringelbach, M (Elsevier, 2017)
When interacting with an infant, parents intuitively enact a range of behaviours that support infant communicative development. These behaviours include altering speech, establishing eye contact and mirroring infant expressions and are argued to occur largely in the absence of conscious intent. Here, we describe studies investigating early, pre-conscious neural responses to infant cues, which we suggest support aspects of parental intuitive behaviour towards infants. This work has provided converging evidence for rapid differentiation of infant cues from other salient social signals in the adult brain. In particular, the orbitofrontal cortex may be important in supporting quick orienting responses and privileged processing of infant cues, processes fundamental to intuitive parenting behaviour.